GrainBot: An Android-Controlled Rice Grain Collector Robot - Masiado , Sunshine L.; Constantino , Anna D.; Cajurao , Jaelord F.; Valenciano , Jayboy V.; Lagayao , Joe Vincent; Dasmariñas , John Sharwin S.; Laud , Renly Jade S. (SOTVI, 2025)
Rice, a fundamental dietary staple for over three billion people around the globe, remains subject to significant postharvest losses, even as advancements in production techniques continue to evolve. Traditional sun drying, although cost-effective and environmentally friendly, presents a range of challenges. It requires considerable labor, exposes farmers to potential health hazards, and often results in uneven drying, which adversely affects grain quality. In response to these pressing issues, this research unveils